1990
DOI: 10.1128/aac.34.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical response of Enterococcus faecalis to the bactericidal activity of penicillin is associated with reduced activity of one autolysin

Abstract: Ten clinical isolates of Enterococcusfaecalis were examined for susceptibility to the bactericidal activity of penicillin. Four of these had MBCs of penicillin equal to 2 to 4x the MIC, and six exhibited a paradoxical response to penicillin, i.e., the bactericidal activity of the anitibiotic had a concentration optimum at 2 to 4x the MIC and decreased significantly at concentrations above this. We found that the paradoxical response to penicillin was an intrinsic and stable property of a strain, but that its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
(12 reference statements)
2
18
1
Order By: Relevance
“…Wild-type cells harboring the pC3 cloning vector exhibited slightly faster autolysis than did untransformed cells, indicating that the presence of a plasmid per se can influence the autolysis kinetics. It has been reported that alterations in autolytic enzyme activity can influence the susceptibility to penicillin (6). We found that the MIC of penicillin for A9 was 6.25 g/ml and was identical to that for the wild type, in both N and BHI media.…”
Section: Vol 177 1995 Gene Controlling Muramidase-2 In E Hirae 5913supporting
confidence: 50%
“…Wild-type cells harboring the pC3 cloning vector exhibited slightly faster autolysis than did untransformed cells, indicating that the presence of a plasmid per se can influence the autolysis kinetics. It has been reported that alterations in autolytic enzyme activity can influence the susceptibility to penicillin (6). We found that the MIC of penicillin for A9 was 6.25 g/ml and was identical to that for the wild type, in both N and BHI media.…”
Section: Vol 177 1995 Gene Controlling Muramidase-2 In E Hirae 5913supporting
confidence: 50%
“…The paradoxical effect (Eagle phenomenon), which was first described by Eagle in 1948, is defined as a bactericidal activity that decreases when the concentration of the antibiotic increases. The mechanism of this phenomenon has not been clearly established; defective autolytic activity when exposed to high concentrations of antibiotics has been implicated for E. faecalis (37). However, the clinical relevance of this phenomenon is still unclear and needs further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…In Enterococcus faecalis, two autolytic activities have been described (12). One of the corresponding proteins, designated AtlA in this report, has been identified (4,18), but its activity has not been characterized.…”
mentioning
confidence: 99%